A three-dimensional vertically aligned carbon nanotube/polyaniline composite as a supercapacitor electrode. Issue 112 (21st November 2016) - Jiao, Shasha; Li, Tiehu; Zhang, Yonggang; Xiong, Chuanyin; Zhao, Tingkai; Khan, Muhammad
Abstract : Highly vertically aligned carbon nanotube arrays grown on the surface of pure titanium plates by chemical vapor deposition serve as substrates for electrodepositing polyaniline to fabricate three-dimensional carbon nanotube/polyaniline composites. Abstract : Highly vertically aligned carbon nanotube arrays grown on the surface of pure titanium plates by chemical vapor deposition serve as substrates for electrodepositing polyaniline, thus fabricating three-dimensional carbon nanotube/polyaniline composites. In addition, X-ray diffraction and Raman spectroscopy are applied to investigate the structures of the as-prepared hybrids. Morphological analysis of the nanotube/polyaniline composites is performed by high resolution SEM and transmission electron microscopy. The combination of the three-dimensional carbon nanotube architecture and conducting polyaniline surprisingly generates a synergistic effect on electrochemical performance which is particularly important. Consequently, the vertically aligned carbon nanotube/polyaniline hybrids exhibit excellent characteristics in terms of specific capacitance (752.5 F g −1 ) and power density (5364 W kg −1 ) at a scanning rate of 100 mV s −1 . Furthermore, the capacity retention can reach over 82% (after 10 000 cycles). This work highlights the critical role of the introduction of vertically laid carbon nanotubes with highly conducting polyaniline in improving the performance of supercapacitors.